Assistance on Gate Construction Work Design and Implementation Aspects in Welding Workshops: Pendampingan Aspek Desain dan Implementasi Pekerjaan Konstruksi Gerbang di Bengkel Las - Nurida Finahari; Gatot Soebiyakto; Gatut Rubiono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The "Moro Mlaku" welding workshop carried out construction work on gate ornaments with 3.5 meters in high and 7.30 meters span. Frame construction with a long span size requires spesific design to obtain safe frame strength. This partner workshop does not have experience handling work like this. This community service activity aims to assist the aspects of the design and implementation of gate construction work in the welding workshop. Activities are carried out using design discussion and assistance methods, material selection, connection types, manufacturing processes as well as transportation and installation. The results of the activities provide positive benefits for partners, especially in terms of increasing knowledge and experience.